(3cJGH aj GdCOHs ((3OeTb s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi GdGFg aEf GdbGVj GdLdjd GdSjO CWGd Gddg HbGAg, hEf cGf aj GdCOH aQO GdOgQ hHOQ GdUOQ s
(3BNQgG (B:s
(3hZQQ SMQ GdHjGf, eeG SeY Hg GdReGf dHYV GdENhGf, hGddg jNJe dfG HGdNjQ s
(3LeY ajg cKjQkG ef GdMce hGdfhGOQ hGdCeKGd fKQkG hfXekGs
(3hQJHg Ydi YTQI CHhGHs
(3hQO aj Chdg Cfg cJGH SMQ GdHjGf hGdfXe GdMGcj bWY GdLeGf dGHf GdhQOj hgPG NWC s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs